2013
DOI: 10.1158/1940-6207.capr-13-0241
|View full text |Cite
|
Sign up to set email alerts
|

Esculetin Suppresses Proliferation of Human Colon Cancer Cells by Directly Targeting β-Catenin

Abstract: The Wnt pathway is a promising therapeutic and preventive target in various human cancers. The transcriptional complex of β-catenin/Tcf, a key mediator of canonical Wnt signaling, has been implicated in human colon cancer development. Current treatment of colon cancer depends on traditional cytotoxic agents with limited effects. Therefore, the identification of natural compounds that can disrupt the β–catenin/TcF complex to suppress cancer cell growth with fewer adverse side effects is needed. To identify comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 44 publications
1
44
0
1
Order By: Relevance
“…Natural coumarins, such as osthole (Zhang et al, 2012), esculetin (Lee et al, 2013), and umbelliferone (Weber et al, 1998) as well as several coumarin containing plant extracts, have been reported to inhibit the growth of cancer cells (Li et al, 2013;Ngo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Natural coumarins, such as osthole (Zhang et al, 2012), esculetin (Lee et al, 2013), and umbelliferone (Weber et al, 1998) as well as several coumarin containing plant extracts, have been reported to inhibit the growth of cancer cells (Li et al, 2013;Ngo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer symptoms include a change in bowel habits or bleeding, but often there are no symptoms. Most colorectal cancers originate from small, noncancerous (benign) tumors called adenomatous polyps that form on the inner walls of the large intestine [13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…A decrease in tumour growth has been reported with esculetin in colon cancer xenograft mouse model. Further, computer docking studies indicated that esculetin disrupted the formation of β-catenin-T cell factor complexes of Wnt signalling pathway (a major pathway in progression of colon cancer) by directly binding to the amino acid residues of β-catenin, thus offering itself as a potent antagonistic agent against β-catenin mediated colon cancer (Lee et al, 2013b).…”
Section: Citrus Limonoids Mechanism Of Anticancer Activity Referencesmentioning
confidence: 99%